PMBOK and Lean Project Management: Criteria, Steps and Logic of the Project Implementation - Anna DOLINSKAIA; Aleksandr KOROLENKO; Viktor NOVOSAD; Anastasiya KAMALOVA (Communications of International Proceedings, 2020)
The main task of the article is to determine the criteria for giving the definition of projects from the point of view of the classic approach – PMBOK and from the point of view of the philosophy of lean production. As part of the study, the phases / stages of project implementation at enterprises were analysed separately. As a conclusion, a generalized scheme of project deployment logic was prepared, and criteria similar in terms of the two directions were defined.
Keywords: Project; Project Management; Lean Manufacturing; Project Approach; A Process Improvement; Implementation Stages; Increasing Productivity.